Controls on Carbon, Nutrient, and Sediment Cycling in a Large, Semiarid Estuarine System; Princess Charlotte Bay, Australia. Issue 1 (10th January 2020) - Crosswell, Joseph R.; Carlin, Geoffrey; Steven, Andy
Abstract: Semiarid estuaries are characterized by pronounced seasonal variability, and a functional understanding of these systems requires constraint of coupled biogeochemical processes and relevant temporal and spatial scales. Here, we integrate 2 years of spatial surveys and time‐series measurements to quantify physical, chemical, and biological drivers in the largest estuarine system in the Great Barrier Reef region. During wet season, freshwater inputs of nutrients and sediment to estuaries were dominated by flood pulses, whereas carbonate input was also influenced by groundwater discharge. This carbonate input counteracted the minimum buffering zone that would otherwise occur at low salinities, thereby decreasing system‐wide air‐water CO2 fluxes. Sediment resuspension was a major control on the transformation and transport of material over tidal and seasonal scales. During wet season, tidal resuspension of benthic algae in nearshore mixing zones acted as an autotrophic filter, removing most bioavailable nutrients from the brackish plume. During dry season, upstream transport combined with hypersaline conditions trapped material in upper estuaries where denitrification and net heterotrophy were high. However, the role of sediment transport varied depending on tidal asymmetry and density‐driven circulation. Estuarine regions with large intertidal areas were dominated by salt flat erosion, which showed a diagenetic signature associated with mid‐Holocene swamp sediments. Tidal resuspension of these organic‐rich sediments appeared to be the dominant control on biogeochemical cycling in coastal waters. This study demonstrates that a holistic understanding of coastal ecosystem connectivity and function requires resolution of both along‐axis and water‐column gradients as well as a range of timescales from tidal to geological cycles. Key Points: Tidal forcing and estuary morphology were the dominant controls on connectivity and the function of filtering and nutrient cycling pathways Tidal asymmetry combined with baroclinic circulation controlled seasonal sediment fluxes in estuaries influencing metabolic and redox cycling Erosion of salt flats exports relic organic matter from a long‐term reservoir to waters where frequent resuspension facilitates degradation